Perancangan Aplikasi Pemesanan Lapangan Badminton Berbasis Web - Clara Zuliani Syahputri; Errissya Rasywir (TIN: Terapan Informatika Nusantara, 2022)
Natasya Badminton Hall, located at Jln. Dr. Purwadi No.rt 13, Kenali Besar, Kec. Kota Baru, Kota Jambi, is one of the badminton courts in Jambi city. The current system for booking badminton courts at Natasya Badminton Hall still relies on manual data recording in books and using an order board. Additionally, for proof of court rental payment, they provide payment receipts.This system has proven to be less effective, often leading to errors in booking and payment transactions. To address these issues, data collection was carried out through observation, interviews, and work documentation. The obtained data was then analyzed to find a solution to the existing problems at Natasya Badminton Hall by designing a web-based badminton court booking application. The development method used for the system is the waterfall model, and various modeling techniques such as use case diagram, activity diagram, and class diagram were employed. The research resulted in a web-based platform for booking badminton courts at Natasya Badminton Hall. With this new system, administrators find it easier to manage court bookings and related data effectively